Changing or upholding the system? : Finnish university students' perceptions on novel wood-based textiles - Hokkanen, Aija (2023)
The clothing and textile industry is one of the most problematic in terms of sustainability: the production value chain harbours a multitude of environmental and social problems, and the rampant success of fast fashion has made consumers buy more clothes than ever in an accelerating pace. To combat these adverse impacts and drive the sustainability transition in the industry circular bioeconomy strategies, practices, and models such as substituting textile materials currently used with more sustainable biobased alternatives should be implemented. These novel textiles have shown great promise in their environmental attributes in increasing the positive climate impact of both the clothing industry and the forest-based industry as well.